Advanced modeling techniques to enhance toilet training in children - Handayani, Indri; Wardani, Septi; Nugroho, Sri Hananto Ponco (Innovation in Health for Society, 2024)
Toilet training in children is a crucial developmental milestone, focusing on teaching them to control defecation and urination. The absence of effective toilet training can result in several challenges, including social embarrassment when interacting with toilet-trained peers and increased stress and anxiety for both the child and parents. This study aims to evaluate the effectiveness of oral and modeling techniques in enhancing toilet training. Utilizing a case study design, we employed participatory observation, unstructured interviews, and documentation to gather data. The sample consisted of a pediatric patient aged 18-24 months. Data analysis was performed using domain analysis after tabulation. The findings indicate that employing oral and modeling techniques significantly improves toilet training outcomes in children. These methods are recommended for parents to implement in-home care settings to facilitate successful toilet training. Keywords: Toilet training; oral techniques; modeling techniques; pediatric care; innovation in pediatric care